Edge-functionalized graphene thermal nanofluids

Edge-functionalized graphene in a water-glycol mixture addresses the challenge of stable dispersion and enhances heat transfer efficiency, achieving up to 50% energy savings in cooling systems.

JP2025500978APending Publication Date: 2025-01-15SICONA BATTERY TECH PTY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024538130
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-23
Filing Date
2022-12-22
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

Existing methods for producing graphene in large quantities for industrial applications face challenges in maintaining desirable properties and achieving stable dispersion in solvents, limiting its use in thermal fluids for cooling systems like server farms.

Method used

Edge-functionalized graphene is combined with water or a water-glycol mixture to form a thermal fluid, enhancing heat transmission and stability, reducing energy consumption in cooling systems.

Benefits of technology

The use of edge-functionalized graphene in thermal fluids significantly improves heat transfer efficiency and reduces energy requirements by up to 50% in cooling systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500978000001_ABST
    Figure 2025500978000001_ABST
Patent Text Reader

Abstract

The present disclosure provides a composition for use as a thermal fluid, the composition comprising: a quantity of dispersible graphene platelets comprising a base layer of graphene, at least one discontinuous graphene layer being stacked on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer being at least partially functionalized; and a quantity of a carrier fluid comprising water.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims convention priority to Australian Provisional Patent Application No. 2021904251, filed December 23, 2021. The contents of AU'251 are incorporated herein by reference in their entirety.

[0002] The present disclosure relates to the use of Applicant's novel edge-functionalized graphene, and more particularly, to its use as a thermal fluid for cooling server farms and the like.

[0003] The present invention will be described with reference to preferred embodiments thereof, but those skilled in the art will recognize that the spirit and scope of the invention can be embodied in many other forms. [Background technology]

[0004] Any discussion of prior art throughout this specification should in no way be taken as an admission that such prior art is widely known or forms part of the common general knowledge in the art.

[0005] Novel edge-functionalized graphenes are described in PCT / AU2019 / 051076 and related national phase applications, each of which is currently assigned to the present applicant.

[0006] PCT / AU2019 / 051076 teaches dispersible graphene platelets and methods for making same. The graphene platelet structure includes a base layer of graphene on which at least one discontinuous layer of graphene is deposited, each layer of graphene on the base layer having a smaller surface area than the layer on which it is deposited. The edges of the base layer and the discontinuous layers deposited thereon are all at least partially functionalized to provide a structure with graphene-like properties due to the base layer and relatively high dispersibility due to the increased amount of functionalized groups on each platelet. Among other uses, the platelets were believed to be useful in the production of electrodes or composite materials.

[0007] Generally, graphene is a carbon film that is one atomic layer thick and has many desirable properties, including high thermal and electrical conductivity, and high mechanical strength. Graphene is therefore a promising material for a wide range of applications such as energy storage, biological sensing and filtration, as well as improved electrical and medical devices. However, the use of graphene in these applications is currently limited by the difficulty of producing and storing large quantities of graphene or graphene derivatives such as nanoplatelets and nanoribbons for industrial-scale manufacturing while maintaining graphene's desirable properties. The term graphene is generally accepted to refer to carbon films (and related materials) that are 1-10 atomic layers thick. Thus, it will be understood that throughout this specification graphene refers to carbon films up to 10 atomic layers. Carbon films with more than 10 atomic layers are typically referred to as graphite.

[0008] Since graphene was first isolated by mechanical cleavage via the "Scotch tape" method, in which adhesive tape is used to peel off layers of graphene from bulk graphite, many processing routes, such as chemical vapor deposition and ball milling, have been investigated with the aim of providing an efficient way to produce large quantities of graphene on an industrial scale, but currently few have proven viable.

[0009] The Hummers process, developed in the 1950s to produce graphite oxide, has been modified to produce large quantities of graphene oxide. Attempts have been made to convert graphene oxide to graphene by reduction. However, to date, graphene oxide has not been successfully reduced to graphene, and although it can be produced in large quantities, it has suboptimal properties compared to natural graphene.

[0010] One promising production route is liquid-phase exfoliation. In this method, graphite is exfoliated into graphene in a liquid medium, often using sonication. Ultrasound can break down the layers of graphene, as they are held together by weak van der Waals forces. This can be further improved by modifying the composition of the liquid medium to include solvents or stabilizers to reduce the potential energy barrier between the sheets.

[0011] The problem with graphene produced by liquid-phase exfoliation is that the graphene structure has poor dispersibility, which requires large amounts of solvent. For example, pure graphene can only be dispersed in pure water at concentrations below 0.01 g / L, and this limit is not significantly improved by the addition of surfactants or constant stirring. Above these concentrations, graphene tends to aggregate and stack again into a graphitic structure. Therefore, it is not practical to store graphene for long periods of time, due to the large amounts of solvent required. A form of graphene that allows for more stable dispersion in water while retaining graphene's beneficial properties, such as electrical conductivity, is therefore desired.

[0012] Using graphene structures in composites also poses challenges due to their tendency to aggregate. Often, it is desirable to have a uniform distribution of a dispersed phase, such as graphene, within a matrix of another material, such as a polymer, to improve the properties of the matrix material, such as strength and electrical conductivity. A stable dispersion of graphene structures facilitates the fabrication of graphene composites with higher concentrations of the dispersed phase, allowing for greater tuning of the material properties of the composite.

[0013] A means of increasing the dispersibility of graphene structures is to functionalize the edges of the graphene sheets, which allows the structures to substantially retain the properties of native graphene while increasing dispersibility. These structures are often referred to as edge-functionalized graphene, as discussed above.

[0014] Apart from the method described by the applicant in PCT / AU2019 / 051076, another method for producing edge-functionalized graphene was described by Ding et al. Sci. Rep. 8:5567 (2018). The method involves adding graphite powder to degassed water, sonicating the mixture to produce a black graphite slurry, mechanically stirring the slurry under heat to steam exfoliate the slurry to functionalize the edges of the platelets, and purifying the resulting mixture by cooling, dilution, and sonication. This produced nanoplatelets several layers thick with hydroxyl groups on the edges. These edge groups allow the platelets to be dispersed in water at concentrations up to 0.55 g / mL. This indicates an improvement in the dispersibility of the graphene structure, but still requires a large amount of solvent. Thus, a graphene structure with better dispersibility was formally taught by the applicant in PCT / AU2019 / 051076.

[0015] A thermic fluid is a gas or liquid that facilitates thermal transfer by acting as a medium for cooling on one side of a process, transporting and storing thermal energy, and heating on the other side of a process. Thermic fluids are used, usually in closed circuits and continuous cycles, in a myriad of applications and industrial processes that require heating or cooling. For example, cooling water cools engines, and heating water in hydronic heating systems heats radiators in rooms. Water is the most common thermic fluid due to its economy, high heat capacity, and favorable transport properties. However, depending on the pressure in the system, it freezes below 0°C and boils at higher temperatures, limiting its useful temperature range. The use of antifreeze additives can alleviate the freezing problem to some extent. However, many other thermic fluids have been developed and are used in a wide variety of applications.

[0016] At high temperatures, oils, synthetic hydrocarbons, or silicone-based fluids have low vapor pressures. Molten salts and metals can be used to transfer and store heat at temperatures above 300-400 °C, where organic fluids begin to decompose. Gases such as water vapor, nitrogen, argon, helium, and hydrogen have been used as thermal fluids when liquids are not suitable. For gases, increased pressure is usually required to facilitate higher flow rates with lower pumping power.

[0017] Server farms represent a modern-day challenge for thermal fluids. A server farm is a collection of computer servers typically maintained by an organization to provide server functionality that far exceeds the capabilities of a single machine. Server farms often consist of thousands of computers, which require large amounts of power to run, generate large amounts of heat, and also require large amounts of power to cool the server farm to maintain efficiency. Server farms typically mount computers, routers, power supplies, and associated electronics in 19-inch racks in a server room or data center. Because space is at a premium, server racks must be housed as close to each other as possible. However, this creates significant problems with airflow, heating, and cooling.

[0018] Server performance is increasing, but so is server power consumption, despite efforts to design lower power integrated circuits. For example, one of the most widely used server processors operates at a maximum of 95 watts. Another server processor operates at 110-165 watts. However, the processor is only one part of the server; other components within the server, such as storage devices, consume additional power, and all components contribute to the overall heat generation.

[0019] To reliably operate servers, especially fanless servers, the data center room must be maintained at an acceptable temperature and humidity. A tightly stacked rack of servers with the latest processors can consume anywhere from 7,000 to 15,000 watts of power. As a result, server racks can generate a very concentrated heat load. The heat dissipated by the servers in the rack is exhausted into the data center room. The overall heat generated by a tightly packed rack can adversely affect the performance and reliability of the equipment in the rack, as it relies on the surrounding air for cooling. Heating, ventilation, and air conditioning (HVAC) systems are therefore often a critical part of an efficient data center design.

[0020] In a data center room, server racks are typically arranged in rows with alternating cold and hot aisles. All servers are mounted within the racks to achieve a front-to-back airflow pattern that draws in conditioned air from the cold rows in front of the racks and expels heat from the hot rows behind the racks. A raised floor room design is commonly used to accommodate an under-floor air distribution system, with cool air provided by raised floor vents along the cold aisles.

[0021] A key element to efficiently cooling a data center is managing the air flow and circulation within the data center. Computer room air conditioner (CRAC) units deliver cool air through floor tiles containing vents between the racks. In addition to the servers, the CRAC units also consume a large amount of power. A single CRAC unit may have up to three 5 horsepower motors, and up to 150 CRAC units may be needed to cool a data center. Collectively, the CRAC units consume a large amount of power within a data center. For example, in a data center room with a hot and cold row configuration, hot air from the hot row is moved out of the hot row and circulated to the CRAC units. The CRAC units cool the air. Fans driven by the motors in the CRAC units deliver the cooled air to an underfloor plenum defined by a raised subfloor. The pressure created by forcing the cooled air into the underfloor plenum forces the cooled air upwards through vents in the subfloor to the cold aisle where the server racks face. To achieve sufficient airflow, hundreds of powerful CRAC units may be installed throughout a typical data center room. However, CRAC units are usually installed in the corners of the data center room, which negatively impacts their ability to efficiently increase airflow. High floors are generally more expensive to build and generally result in lower cooling efficiency due to inefficient air movement within the data center room. Additionally, the location of floor vents must be carefully planned throughout the design and construction of the data center to prevent short-circuiting of the supply air.

[0022] It is an object of the present invention to overcome or ameliorate at least one of the disadvantages of the prior art, or to provide a useful alternative.

[0023] It is an object of particularly preferred forms of the invention to provide a composition suitable for use as a thermal fluid, for example for use in cooling data centers, radiators or air conditioners. Due to the cost and favorable thermal properties of water, it is believed that water should constitute the majority component of the composition. Unless the context clearly requires otherwise, throughout the description and claims, the words "comprise", "comprising", and the like, are to be construed in their inclusive sense, i.e., "including but not limited to," rather than in their exclusive or exhaustive sense. Although the invention will be described with reference to specific examples, those skilled in the art will appreciate that the invention can be embodied in many other forms. [Prior art documents] [Patent documents]

[0024] [Patent Document 1] PCT / AU2019 / 051076 [Non-patent literature]

[0025] [Non-Patent Document 1] Ding et al.Sci.Rep.8:5567(2018) Summary of the Invention

[0026] The inventors have surprisingly discovered that edge-functionalized graphene of the type described in PCT / AU2019 / 051076 forms an efficient thermal fluid when combined with about 0.25-1.0 wt.% water or water-glycol. Surprisingly, this combination of features has been found to be effective in significantly reducing the energy required to cool the composition and increasing the efficiency with which the composition transports heat.

[0027] The use of edge-functionalized graphene has been found to increase the permeability of heat into the composition. The edge-functionalized graphene is capable of hydrogen bonding with surrounding water molecules to form a substantially homogeneous solution. Such a solution can transport heat more efficiently, increasing the amount of heat that the solution can absorb in a shortened time frame and reducing the energy required to remove heat from the solution when needed.

[0028] The amount of edge-functionalized graphene needed to induce the effect is only 0.01 wt%, but the effect plateaus above about 5-6 wt%. The ideal range was found to be 0.25-1 wt%.

[0029] Additionally, it has been found that increasing the concentration of edge-functionalized graphene can increase the viscosity of the composition, although not enough to affect its use in most, if not all, cooling systems.

[0030] Using the edge-functionalized graphene blend in cooling systems has the potential to reduce energy use by up to 50%. In the right commercial context, even a 2% efficiency improvement could be game-changing.

[0031] The compositions may contain other ingredients such as propylene glycol, ethylene glycol, ethanol, methanol, propanol, etc. These may be present in any mixture at about 0.01% to 50% by weight, preferably up to 30% by weight. Other ingredients may include alcohols, surfactants, dyes, or weak acids or bases. The purpose of the other ingredients is to increase the boiling point elevation, reduce the freezing point depression, make the mixture easily identifiable in case of a leak, or to solubilize / make a salt out of any of the ingredients.

[0032] Finally, although edge-functionalized graphene is stable in solution, surfactants / stabilizers may enhance stability, especially over time.

[0033] According to a first aspect of the present invention there is provided a composition for use as a thermal fluid, the composition comprising: a) a quantity of dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) Contains a dispersion medium that contains a certain amount of water.

[0034] In one embodiment, the dispersible graphene platelets include defined central and edge regions, where the edge region is at least partially functionalized and the central region is at least partially unfunctionalized.

[0035] In one embodiment, the amount of dispersed graphene platelets is from about 0.1 to about 6% by weight of the composition.

[0036] In one embodiment, the amount of dispersed graphene platelets is about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or about 6% by weight.

[0037] In one embodiment, water can be in any desired amount, preferably 1 to 99% by weight based on the total weight of the composition, including all values ​​and sub-ranges therebetween, including 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 85, 90, 95, 96, 97, 98, 99% by weight. More preferably, the amount of water ranges from 94 to 99.9% by weight, most preferably from 99 to 99.9% by weight. Preferably, the water is distilled and / or deionized. Preferably, the water is deionized prior to contact with other components of the composition.

[0038] In one embodiment, the amount of dispersed graphene platelets is from about 0.1 to about 1% by weight of the composition.

[0039] In one embodiment, the amount of dispersed graphene platelets is from about 0.2 to about 0.9 wt.%, from about 0.3 to about 0.8 wt.%, from about 0.4 to about 0.7 wt.%, or from about 0.5 to about 0.6 wt.% of the composition.

[0040] In one embodiment, the amount of dispersed graphene platelets is from about 0.25 to about 1% by weight of the composition.

[0041] In one embodiment, the dispersion medium further comprises one or more co-solvents.

[0042] In one embodiment, the one or more co-solvents are selected from glycols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, hexylene glycol, diethylene glycol, di-propylene glycol, or glycerin, of which ethylene glycol and propylene glycol are preferred due to their chemical stability and low cost.

[0043] In one embodiment, the one or more co-solvents can be glyme, diglyme, etc., which can elicit an effect similar to that of glycols.

[0044] In one embodiment, the one or more co-solvents are selected from at least one component selected from hexanoic acid, heptanoic acid and their salts, and alkyl benzoic acid having C1-C5 alkyl and their salts. Hexanoic acid, heptanoic acid and their salts each have excellent corrosion inhibition properties for aluminum and iron, and can effectively prevent cavitation in the cooling system in cooperation with at least one component selected from the group of alkyl benzoic acid having C1-C5 alkyl and their salts.

[0045] In one embodiment, the salts of hexanoic acid and heptanoic acid may be their alkali metal, ammonium or amine salts, of which the alkali metal salts are preferred. The preferred alkali metal salts are the sodium and potassium salts. Multiples of these chemicals may be mixed in the compositions of the present invention.

[0046] In one embodiment, hexanoic acid, heptanoic acid and / or salts thereof are mixed in the composition of the present invention in a total amount of about 0.1 to 5.0% by weight. If the amount is less than this range, prevention of metal corrosion and cavitation is insufficient, and if the amount is more than this range, it may become uneconomical.

[0047] In one embodiment, alkyl benzoic acids having C1-C5 alkyl groups and their salts can individually inhibit metal corrosion, particularly aluminum and iron corrosion, and can cooperate with hexanoic acid, heptanoic acid and / or their salts to inhibit cavitation in cooling systems, and can individually inhibit precipitation of hard water minerals in the coolant.

[0048] In one embodiment, the alkyl benzoic acid having C1-C5 alkyl may be p-toluic acid, p-ethyl benzoic acid, p-propyl benzoic acid, p-isopropyl benzoic acid, p-butyl benzoic acid, or p-tert-butyl benzoic acid. The salt of the alkyl benzoic acid having C1-C5 alkyl may be an alkali metal salt, an ammonium salt, an amine salt, or the like, among which an alkali metal salt such as a sodium salt or a potassium salt is preferred, and a plurality of these salts may be mixed.

[0049] In one embodiment, the alkyl benzoic acid and / or its salt having C1-C5 alkyl may be mixed in the composition of the present invention in a total amount of about 0.1-5.0% by weight, either singly or in combination. If the amount is less than this range, it may be ineffective in suppressing metal corrosion and cavitation, and if the amount is more than this range, it may be uneconomical.

[0050] In one embodiment, one or more triazoles may also be added to effectively inhibit the corrosion of metals in the cooling system, especially copper and aluminum, such triazoles being preferably selected from benzotriazole, tolyltriazole, 4-phenyl-1,2,3-triazole and 2-naphthotriazole, or 4-nitrobenzotriazole.

[0051] In one embodiment, the triazole(s) may be mixed in an amount of about 0.05 to 1.0% by weight, below that range the inhibition of metal corrosion may be insufficient, and above that range it may become uneconomical.

[0052] In one embodiment, the compositions of the present invention may be characterized as optionally being free of certain components, namely, amine salts or borates, which prevent the formation of nitrosamines in the coolant, and the absence of borates which reduces corrosion of aluminum and aluminum alloys.

[0053] In one embodiment, the composition may optionally and selectively include an antifoaming agent and / or a colorant and / or a conventional metal corrosion inhibitor such as molybdates, tungstates, sulfates, nitrates, mercaptobenzothiazoles, or alkali metal salts thereof.

[0054] In one embodiment, the one or more co-solvents are ethylene glycol or propylene glycol. Preferably, the one or more co-solvents are ethylene glycol.

[0055] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 50:50.

[0056] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 60:40.

[0057] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 70:30.

[0058] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 80:20.

[0059] In one embodiment, the one or more co-solvents used can be in any desired amount, preferably 1 to 99 weight percent based on the total weight of the composition, including all values ​​and sub-ranges therebetween, including 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 85, 90, 95, 96, 97, 98, 99 weight percent.

[0060] In one embodiment, the composition of the present invention further comprises at least one fluorosurfactant in an amount of 0.001 to 50 wt.% based on the total weight of the composition, which may be 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4 , 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 wt %, including all values ​​and subranges therebetween. The fluorosurfactant desirably causes a decrease in contact angle (e.g., drop height) compared to an untreated water / glycol mixture, modifies the surface properties of a liquid or solid, or reduces the surface tension of a fluid or the interfacial tension between two immiscible fluids, such as oil and water. Preferably, the fluorosurfactant is soluble in water. Preferred fluorosurfactants include, but are not limited to, Zonyl fluorosurfactants (anionic, nonionic and amphoteric fluorinated surfactants), including Zonyl FSA, FSE, FSJ, FSP, TBS, FSO, FSH, FSN, FSD and FSK, more preferably nonionic Zonyl fluorosurfactants, most preferably Zonyl FSH, FSN or FSP (typically a mixture of polyethylene glycol substituted with a fluoroalkyl alcohol, water and a glycol ether such as glycol or dipropylene glycol methyl ether). The fluorosurfactants can be used alone or in combination with other fluorosurfactants or non-fluorosurfactants as required.

[0061] In one embodiment, when a defoamer is present, the defoamer can be used in an amount sufficient to reduce foam buildup or to reduce foam or trapped air by bursting the foam to release the trapped air. Preferably, the antifoaming agent is used in an amount of 0.01 to 50 weight percent based on the total weight of the composition, including all values ​​and sub-ranges therebetween, including 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 and 50 weight percent. One or more defoamers may be present. Preferred defoamers include, but are not limited to, ethylene glycol n-butyl ether based defoamers, silicone emulsions, hydrocarbon oil emulsions, EO / PO copolymers, and oil soluble, water miscible defoamers.

[0062] In one embodiment, the composition comprises one or more corrosion inhibitors in an amount sufficient to inhibit or reduce corrosion of an exposed metal surface in contact with the composition of the present invention, preferably in an amount of 0.01 to 50 wt.%, based on the total weight of the composition, including 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 weight percent, including all values ​​and subranges therebetween. Preferred corrosion inhibitors include any conventionally or commercially used corrosion inhibitor, including, but not limited to, for example, sodium nitrate, sodium nitrite, azonitrile, dipotassium phosphate, sodium benzoate, and mixtures thereof. More preferably, the corrosion inhibitor is an aqueous solution of a nitrite, a nitrate, and sodium hydroxide.

[0063] In one embodiment, the composition may include a colorant to allow the user to easily distinguish the composition from colorless liquids, particularly water. Suitable colorants may be any conventional colorant and may be any desired color, including, but not limited to, orange, blue, green, red and yellow, and any combination thereof. When present, the dye may be used in any amount to provide the required color, preferably in an amount of 0.01 to 50% by weight based on the total weight of the composition, which may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 7 , 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 weight percent, including all values ​​and subranges therebetween. One or more dyes may be present. More preferably, any light stable, transparent, water soluble organic dye is suitable, including but not limited to, acid red dye, methylene blue, uranine dye, wool yellow dye, and rhodamine dye, which are particularly preferred.

[0064] In one embodiment, the pH of the composition may be adjusted as necessary. Any compound that is pH active may be suitably used and selected according to what is known in the art. The pH may range from 3 to 11, including all values ​​and subranges therebetween, including 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5. The preferred pH adjuster is aminomethylpropanol. Preferably, the pH is adjusted to avoid the use of reserve alkalinity of the corrosion inhibitor or corrosion inhibitor composition.

[0065] In one embodiment, the platelets are capable of forming a stable dispersion in water at a concentration of up to 700 mg / mL.

[0066] In one embodiment, the electrical conductivity of the platelets is about 900 S / cm.

[0067] In one embodiment, the platelets are further functionalized by adding metal ions to at least one of the functionalized edges or surfaces.

[0068] In one embodiment, the metal ions are selected from Fe, Cu, Co and Sn.

[0069] According to a second aspect of the present invention there is provided a composition for use as a thermal fluid, the composition comprising: a) a quantity of a polymer matrix composite comprising a polymer and dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) Contains a dispersion medium that contains a certain amount of water.

[0070] In one embodiment, the dispersible graphene platelets include defined central and edge regions, where the edge region is at least partially functionalized and the central region is at least partially unfunctionalized.

[0071] In one embodiment, the amount of dispersed graphene platelets is from about 0.1 to about 6% by weight of the composition.

[0072] In one embodiment, the amount of dispersed graphene platelets is from about 0.25 to about 1% by weight of the composition.

[0073] In one embodiment, the dispersion medium further comprises one or more co-solvents.

[0074] In one embodiment, the one or more co-solvents are selected from glycols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, hexylene glycol, diethylene glycol, di-propylene glycol, or glycerin, of which ethylene glycol and propylene glycol are preferred due to their chemical stability and low cost.

[0075] In one embodiment, the one or more co-solvents are selected from at least one component selected from hexanoic acid, heptanoic acid and their salts, and alkyl benzoic acid having C1-C5 alkyl and their salts. Hexanoic acid, heptanoic acid and their salts each have excellent corrosion inhibition properties for aluminum and iron, and can effectively prevent cavitation in the cooling system in cooperation with at least one component selected from the group of alkyl benzoic acid having C1-C5 alkyl and their salts.

[0076] In one embodiment, the salts of hexanoic acid and heptanoic acid may be their alkali metal, ammonium or amine salts, of which the alkali metal salts are preferred. The preferred alkali metal salts are the sodium and potassium salts. Multiple of these chemicals may be mixed in the compositions of the present invention.

[0077] In one embodiment, hexanoic acid, heptanoic acid and / or salts thereof are mixed in the composition of the present invention in a total amount of about 0.1 to 5.0% by weight. If the amount is less than this range, prevention of metal corrosion and cavitation is insufficient, and if the amount is more than this range, it may become uneconomical.

[0078] In one embodiment, alkyl benzoic acids having C1-C5 alkyl groups and their salts can individually inhibit metal corrosion, particularly aluminum and iron corrosion, and can cooperate with hexanoic acid, heptanoic acid and / or their salts to inhibit cavitation in cooling systems, and can individually inhibit precipitation of hard water minerals in the coolant.

[0079] In one embodiment, the alkyl benzoic acid having C1-C5 alkyl may be p-toluic acid, p-ethyl benzoic acid, p-propyl benzoic acid, p-isopropyl benzoic acid, p-butyl benzoic acid, or p-tert-butyl benzoic acid. The salt of the alkyl benzoic acid having C1-C5 alkyl may be an alkali metal salt, an ammonium salt, an amine salt, or the like, among which an alkali metal salt such as a sodium salt or a potassium salt is preferred, and a plurality of these salts may be mixed.

[0080] In one embodiment, the alkyl benzoic acid and / or its salt having C1-C5 alkyl may be mixed in the composition of the present invention in a total amount of about 0.1-5.0% by weight, either singly or in combination. If the amount is less than this range, it may be ineffective in suppressing metal corrosion and cavitation, and if the amount is more than this range, it may be uneconomical.

[0081] In one embodiment, one or more triazoles may also be added to effectively inhibit the corrosion of metals in the cooling system, especially copper and aluminum, such triazoles being preferably selected from benzotriazole, tolyltriazole, 4-phenyl-1,2,3-triazole and 2-naphthotriazole, or 4-nitrobenzotriazole.

[0082] In one embodiment, the triazole may be mixed in an amount of about 0.05 to 1.0% by weight, below that range the inhibition of metal corrosion may be insufficient, and above that range it may become uneconomical.

[0083] In one embodiment, the compositions of the present invention may be characterized as optionally being free of certain components, namely, amine salts or borates, which prevent the formation of nitrosamines in the coolant, and the absence of borates which reduces corrosion of aluminum and aluminum alloys.

[0084] In one embodiment, the composition may optionally and selectively include an antifoaming agent and / or a colorant and / or a conventional metal corrosion inhibitor such as molybdates, tungstates, sulfates, nitrates, mercaptobenzothiazoles, or alkali metal salts thereof.

[0085] In one embodiment, the one or more co-solvents are ethylene glycol or propylene glycol. Preferably, the one or more co-solvents are ethylene glycol.

[0086] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 50:50.

[0087] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 60:40.

[0088] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 70:30.

[0089] In one embodiment, the dispersion medium comprises water and one or more co-solvents in a weight ratio of about 80:20.

[0090] In one embodiment, the one or more co-solvents used can be in any desired amount, preferably 1 to 99 weight percent based on the total weight of the composition, including all values ​​and sub-ranges therebetween, including 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 85, 90, 95, 96, 97, 98, 99 weight percent.

[0091] In one embodiment, the composition of the present invention further comprises at least one fluorosurfactant in an amount of 0.001 to 50 wt.% based on the total weight of the composition, which may be 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4 , 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 wt %, including all values ​​and subranges therebetween. The fluorosurfactant desirably causes a decrease in contact angle (e.g., drop height) compared to an untreated water / glycol mixture, modifies the surface properties of a liquid or solid, or reduces the surface tension of a fluid or the interfacial tension between two immiscible fluids, such as oil and water. Preferably, the fluorosurfactant is soluble in water. Preferred fluorosurfactants include, but are not limited to, Zonyl fluorosurfactants (anionic, nonionic and amphoteric fluorinated surfactants), including Zonyl FSA, FSE, FSJ, FSP, TBS, FSO, FSH, FSN, FSD and FSK, more preferably nonionic Zonyl fluorosurfactants, most preferably Zonyl FSH, FSN or FSP (typically a mixture of polyethylene glycol substituted with a fluoroalkyl alcohol, water and a glycol ether such as glycol or dipropylene glycol methyl ether). The fluorosurfactants can be used alone or in combination with other fluorosurfactants or non-fluorosurfactants as required.

[0092] In one embodiment, when a defoamer is present, the defoamer can be used in an amount sufficient to reduce foam buildup or to reduce foam or trapped air by bursting the foam to release the trapped air. Preferably, the antifoaming agent is used in an amount of 0.01 to 50 weight percent based on the total weight of the composition, including all values ​​and sub-ranges therebetween, including 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 and 50 weight percent. One or more defoamers may be present. Preferred defoamers include, but are not limited to, ethylene glycol n-butyl ether based defoamers, silicone emulsions, hydrocarbon oil emulsions, EO / PO copolymers, and oil soluble, water miscible defoamers.

[0093] In one embodiment, the composition comprises one or more corrosion inhibitors in an amount sufficient to inhibit or reduce corrosion of an exposed metal surface in contact with the composition of the present invention, preferably in an amount of 0.01 to 50 wt.%, based on the total weight of the composition, including 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 weight percent, including all values ​​and subranges therebetween. Preferred corrosion inhibitors include any conventionally or commercially used corrosion inhibitor, including, but not limited to, for example, sodium nitrate, sodium nitrite, azonitrile, dipotassium phosphate, sodium benzoate, and mixtures thereof. More preferably, the corrosion inhibitor is an aqueous solution of a nitrite, a nitrate, and sodium hydroxide.

[0094] In one embodiment, the composition may include a colorant to allow the user to easily distinguish the composition from colorless liquids, particularly water. Suitable colorants may be any conventional colorant and may be any desired color, including, but not limited to, orange, blue, green, red and yellow, and any combination thereof. When present, the dye may be used in any amount to provide the required color, preferably in an amount of 0.01 to 50% by weight based on the total weight of the composition, which may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 7 , 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 weight percent, including all values ​​and subranges therebetween. One or more dyes may be present. More preferably, any light stable, transparent, water soluble organic dye is suitable, including but not limited to, acid red dye, methylene blue, uranine dye, wool yellow dye, and rhodamine dye, which are particularly preferred.

[0095] In one embodiment, the pH of the composition may be adjusted as necessary. Any compound that is pH active may be suitably used and selected according to what is known in the art. The pH may range from 3 to 11, including all values ​​and subranges therebetween, including 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5. The preferred pH adjuster is aminomethylpropanol. Preferably, the pH is adjusted to avoid the use of reserve alkalinity of the corrosion inhibitor or corrosion inhibitor composition.

[0096] In one embodiment, the platelets are capable of forming a stable dispersion in water at a concentration of up to 700 mg / mL.

[0097] In one embodiment, the electrical conductivity of the platelets is about 900 S / cm.

[0098] In one embodiment, the platelets are further functionalized by adding metal ions to at least one of the functionalized edges or surfaces.

[0099] In one embodiment, the metal ions are selected from Fe, Cu, Co and Sn.

[0100] In one embodiment, the platelets are capable of forming a stable dispersion in water at a concentration of up to 700 mg / mL.

[0101] In one embodiment, the electrical conductivity of the platelets is about 900 S / cm.

[0102] In one embodiment, the platelets are further functionalized by adding metal ions to at least one of the functionalized edges or surfaces.

[0103] In one embodiment, the metal ions are selected from Fe, Cu, Co and Sn.

[0104] In one embodiment, the polymer is selected from alginate, chitosan, PVA, PEG, PU, ​​PEI, PVDF, PDMS or PEDOT PSS.

[0105] According to a third aspect of the present invention there is provided a method of producing a composition for use as a thermal fluid, the method comprising the steps of: a) forming a quantity of dispersed graphene platelets comprising a base layer of graphene, at least one discontinuous graphene layer deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer being at least partially functionalized by suspending graphite or graphene in a solution comprising an organic nitrile (such as acetonitrile), an ester (such as ethyl acetate) and water, and reacting the solution comprising the suspended graphite or graphene with an oxidizing agent (such as ruthenium tetroxide) to at least partially functionalize the edge regions of the graphite or graphene; b) forming a dispersion medium comprising a quantity of water; c) mixing a quantity of the dispersed graphene platelets with a quantity of water, thereby producing a substantially homogenous composition.

[0106] In one embodiment, the method further comprises homogenizing the resulting solution to ensure that the dispersible graphene platelets are substantially regularly distributed throughout.

[0107] In one embodiment, the method further comprises cooling the solution obtained in step b in an ice bath.

[0108] In one embodiment, the method further comprises the step of homogenizing the solution obtained in step b.

[0109] In one embodiment, homogenization is carried out at 20000 rpm for up to 2 hours.

[0110] In one embodiment, the method further comprises the step of sonicating the solution obtained in step b.

[0111] In one embodiment, the method further comprises filtering the solution obtained in step b to produce a filtered solid.

[0112] In one embodiment, the method further comprises washing the filtered solids.

[0113] In one embodiment, the method further comprises washing the filtered solid with HCl and water.

[0114] In one embodiment, the filtered solid is washed with HCl until the filtrate obtained by washing the filtered solid is colorless, and then washed with water until the filtrate is neutral.

[0115] In one embodiment, the filtered solid is washed with an organic solvent, such as ethanol or acetone.

[0116] In one embodiment, the filtered solids are dried in vacuum to produce a dry powder.

[0117] In one embodiment, the filtered solids are lyophilized to produce a dry powder.

[0118] In one embodiment, the dry powder is dispersed in water and sonicated for up to 30 minutes, and the resulting mixture is allowed to stand for up to 48 hours to produce a solid and a supernatant, which is decanted and filtered to produce the graphene powder.

[0119] In one embodiment, the graphene powder is washed with an organic solvent and dried.

[0120] In one embodiment, the dry powder is dispersed in water and sonicated for up to 30 minutes, and the resulting mixture is centrifuged to produce a solid and a supernatant.

[0121] In one embodiment, the oxidizing agent is ruthenium tetroxide.

[0122] In one embodiment, ruthenium tetroxide is obtained by reaction of sodium periodate with ruthenium chloride added to a solution containing suspended graphene or graphite.

[0123] In one embodiment, the graphene or graphite is provided in the form of expanded graphite, which has an increased interlayer spacing.

[0124] In one embodiment, the filtered solid is then dispersed in a solution containing metal ions to bind the metal ions to at least one of the surfaces or functionalized edges of the platelets.

[0125] In one embodiment, the metal ions are selected from Fe, Cu, Co and Sn.

[0126] According to a fourth aspect of the present invention there is provided a method of producing a composition for use as a thermal fluid, the method comprising the steps of:

[0127] a) forming a quantity of a polymer matrix composite comprising a polymer and dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) forming a dispersion medium comprising a quantity of water; c) mixing a quantity of the dispersed graphene platelets with a quantity of water, thereby producing a substantially homogenous composition.

[0128] In one embodiment, the method further comprises homogenizing the resulting solution to ensure that the dispersible graphene platelets are substantially regularly distributed throughout.

[0129] In one embodiment, the method further comprises cooling the solution obtained in step b in an ice bath.

[0130] In one embodiment, the method further comprises the step of homogenizing the solution obtained in step b.

[0131] In one embodiment, homogenization is carried out at 20000 rpm for up to 2 hours.

[0132] In one embodiment, the method further comprises the step of sonicating the solution obtained in step b.

[0133] In one embodiment, the method further comprises filtering the solution obtained in step b to produce a filtered solid.

[0134] In one embodiment, the method further comprises washing the filtered solids.

[0135] In one embodiment, the method further comprises washing the filtered solid with HCl and water.

[0136] In one embodiment, the filtered solid is washed with HCl until the filtrate obtained by washing the filtered solid is colorless, and then washed with water until the filtrate is neutral.

[0137] In one embodiment, the filtered solid is washed with an organic solvent, such as ethanol or acetone.

[0138] In one embodiment, the filtered solids are dried in vacuum to produce a dry powder.

[0139] In one embodiment, the filtered solids are lyophilized to produce a dry powder.

[0140] In one embodiment, the dry powder is dispersed in water and sonicated for up to 30 minutes, and the resulting mixture is allowed to stand for up to 48 hours to produce a solid and a supernatant, which is decanted and filtered to produce the graphene powder.

[0141] In one embodiment, the graphene powder is washed with an organic solvent and dried.

[0142] In one embodiment, the dry powder is dispersed in water and sonicated for up to 30 minutes, and the resulting mixture is centrifuged to produce a solid and a supernatant.

[0143] In one embodiment, the oxidizing agent is ruthenium tetroxide.

[0144] In one embodiment, ruthenium tetroxide is obtained by reaction of sodium periodate with ruthenium chloride added to a solution containing suspended graphene or graphite.

[0145] In one embodiment, the graphene or graphite is provided in the form of expanded graphite, which has an increased interlayer spacing.

[0146] In one embodiment, the filtered solid is then dispersed in a solution containing metal ions to bind the metal ions to at least one of the surfaces or functionalized edges of the platelets.

[0147] In one embodiment, the metal ions are selected from Fe, Cu, Co and Sn.

[0148] According to a fifth aspect of the invention there is provided a composition according to the first aspect of the invention when produced by a method according to the third aspect of the invention.

[0149] According to a sixth aspect of the invention there is provided a composition according to the second aspect of the invention when produced by a method according to the fourth aspect of the invention.

[0150] Preferred embodiments of the invention will now be described with reference to the following representative and non-limiting figures. [Brief description of the drawings]

[0151] [Figure 1] FIG. 1 shows a schematic diagram of dispersive graphene platelets. [Diagram 2] A low magnification bright field TEM image of a single dispersed graphene platelet is shown. [Diagram 3] 1 shows a high magnification bright field TEM image of the edge of a dispersive graphene platelet. [Figure 4]1 shows an SEM image of dispersible graphene platelets at 5000x magnification. [Figure 5A] 1 shows the Raman spectrum of a graphene platelet sample. [Figure 5B] The Raman spectrum of 99.9999% graphite is shown. [Figure 6A] 1 shows extended 2D bands from the Raman spectrum of the edge of a dispersive graphene platelet. [Figure 6B] FIG. 1 shows extended 2D bands from the Raman spectrum of the basal plane of dispersive graphene platelets. [Figure 7A] 1 shows the XRD spectrum of a graphene platelet sample. [Figure 7B] XRD spectra of both 99.9999% graphite and graphene platelets are shown. [Figure 8] 1 shows an XPS spectrum of a graphene platelet sample. [Figure 9] 1 shows a graph of the titration of a dispersion of graphene platelets. [Figure 10] TEM images of EFG at low and high magnification are shown. a) The image displays several EFG NPs. b) Bright field image of a typical EFG NP. c) and d) High resolution images of the edge of a typical sheet confirming the presence of 1-4 layers. Note in c) the edge of the EFG showing a monolayer, whereas in d) two layers are visible. e) Bright field (BF) image and f) Annular dark field (HAADF) image at the edge of a typical EFG platelet. (i), (ii), (iii) show monolayer, bilayer, and trilayer, respectively, while (iv) represents an oxygen-rich region at the edge. In (i)-(iii), the diffraction increases with the increasing number of layers, whereas at the edge (iv), the higher diffraction is a result of the presence of heavier atoms (probably two oxygen atoms stacked to form a COOH group). [Figure 11] The reference data applied to the data farm's current modeling is shown below. The Cp of pure graphene is about 7-20 J / kmol. [Figure 12]1 shows the thermal analysis report of 0.25 wt% edge-functionalized graphene in 70:30 water:ethylene glycol. [Figure 13] 1 shows the thermal analysis report of 0.5 wt % edge-functionalized graphene in 70:30 water:ethylene glycol. [Figure 14] 1 shows the thermal analysis report of 0.75 wt% edge-functionalized graphene in 70:30 water:ethylene glycol. [Figure 15A] The design criteria for data center cooling modeling performed by applicant shows: 42 servers per rack, 100 racks, 12kW power input per rack, 4200 servers, 287W heat generated per server, and 1205W total heat generated by each server rack. [Figure 15B] The design criteria for data center cooling modeling performed by applicant shows: 42 servers per rack, 100 racks, 12kW power input per rack, 4200 servers, 287W heat generated per server, and 1205W total heat generated by each server rack. [Figure 15C] The design criteria for data center cooling modeling performed by applicant shows: 42 servers per rack, 100 racks, 12kW power input per rack, 4200 servers, 287W heat generated per server, and 1205W total heat generated by each server rack. [Figure 15D] The design criteria for data center cooling modeling performed by applicant shows: 42 servers per rack, 100 racks, 12kW power input per rack, 4200 servers, 287W heat generated per server, and 1205W total heat generated by each server rack. [Figure 15E] The design criteria for data center cooling modeling performed by applicant shows: 42 servers per rack, 100 racks, 12kW power input per rack, 4200 servers, 287W heat generated per server, and 1205W total heat generated by each server rack. [Figure 16]The thermal performance of edge-functionalized graphene thermal fluids at concentrations of 0-5 wt% is shown. The data shows that the conductive component edge-functionalized graphene plays a key role in improving heat rejection and thermal performance. [Figure 17A] Map the increase in thermal coefficient (%) against the estimated decrease in thermal area (%) from edge-functionalized graphene concentrations between approximately 0 and 5 wt%. [Figure 17B] The assumptions made in Figure 17A are tested by plotting the calculated Cp and the Cp from the thermal test results. [Figure 18] The capacity requirements for the cooling pump are shown for flow rates from about 100 m3 / hr to about 225 m3 / hr. [Figure 19] The relationship between enthalpy and temperature in the cooling tower modeling used in this simulation is shown. [Figure 20] High level cooling tower area estimations across edge-functionalized graphene concentrations of 0.25, 0.5, 0.75, 1, 1.25, 1.5, 2 and 5 wt% are shown. [Figure 21] It shows calculations performed modeling 4000 servers and the power output allocation calculated to be 36.58% for the servers / mainframes. [Figure 22] It shows the same power allocation as in Figure 21, for which annual energy savings data were calculated. [Diagram 23] The reduction in power consumption expected when using edge-functionalized graphene thermal fluids of the present invention is shown. It can be clearly seen that the savings are most significant at concentrations between about 0.25% and about 1% by weight. These data were obtained using edge-functionalized graphene in a 70:30 water / ethylene glycol dispersion medium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0152] The present invention provides a composition for use as a thermal fluid, the composition comprising:

[0153] a) a quantity of dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) Contains a dispersion medium that contains a certain amount of water.

[0154] The amount of dispersed graphene platelets ranges from about 0.1 to about 6% by weight of the composition, with empirical modeling data indicating that an amount of from about 0.25 to about 1% by weight is optimal.

[0155] Preferably, the dispersion medium is water, and the volume ratio of water to ethylene glycol or propylene glycol may be about 70:30.

[0156] As mentioned above, one or more co-solvents may be added to the composition, such as glycols, alcohols, surfactants, dyes, defoamers, acids, bases, and the like.

[0157] Thermal Analysis Labs (TAL) conducted calorimetric and thermal conductivity analysis of nine compositions of edge-functionalized graphene in 70:30 water / ethylene glycol as described above for the carrier medium, and the data is shown in Table 1 below. [Table 1]

[0158] The data obtained above was used to model potential energy savings applicable to data centers, as shown in the accompanying Figures 11-23. In particular, Figure 23 shows that annual energy savings of about 10 to about 50% are achievable using thermal fluids described in the present invention at concentrations ranging from about 0.25 to about 1 wt%. The energy savings above about 1 wt% edge-functionalized graphene are less significant, suggesting that the optimal concentration of edge-functionalized graphene in 70:30 water / ethylene glycol is about 0.2 to about 1 wt%.

[0159] Based on the data, several conclusions can be reached: increasing edge-functionalized graphene composition improves thermal performance, with the most likely optimal composition being in the range of 0.25-1 wt% or less; edge-functionalized graphene thermal fluids improve heat rejection within cooling towers, thereby reducing data center energy usage, with estimated annual energy savings ranging from about 15% to about 30% (for edge-functionalized graphene concentrations of 0.25-0.75 wt%); and, most commercially important, edge-functionalized graphene may enable conventional and future data center cooling systems to achieve significant improvements in heat rejection performance, energy savings, and cost reductions.

[0160] Dispersible graphene platelets have a structure that includes a base layer of micron-scale graphene. On the surface of this base layer are irregular nanometer-sized graphene layers that can be stacked as high as 7-9 layers above the base layer. Stated differently, the structure includes a base layer of graphene with at least one discontinuous layer of graphene stacked on top, where each layer of graphene in the base layer has a smaller surface area than the layer it is stacked on. The edges of the base layer and the discontinuous layers stacked on top of it are all at least partially functionalized to provide the structure with graphene-like properties from the base layer and increased dispersibility due to the increased amount of functionalized groups on each platelet.

[0161] 1 and 2-4 show schematic diagrams and microscopic images, respectively, of a dispersible graphene platelet 10. The base graphene layer 1 is micron-sized and features functional groups 5, such as hydroxyl or carboxylic acids, around its edges. The platelet 10 further includes a discontinuous graphene layer 2 deposited on the surface of the base layer 1. Further discontinuous graphene layers 3 and 4 are deposited on top of layer 2, with each discontinuous layer having a reduced surface area relative to the layer below it. The edges of each discontinuous layer are also characterized by a degree of functionalization in the form of functionalizing groups 5.

[0162] In a preferred embodiment, RuO4 can be used as an oxidizing agent to functionalize the edges of graphene platelets. RuO4 is suitable for strong and selective oxidation effect, and can partially convert the outermost ring of graphene structure to carboxylic acid or phenol without modifying the inner structure. RuO4 can be provided to graphene or graphite by the reaction of RuCl3 and NaIO4 in solution.

[0163] In another preferred embodiment, the graphite used to produce the dispersible graphene platelets can first be thermally expanded to increase the interlayer spacing before being placed in solution. This can be carried out at temperatures between 700 and 1000° C., in one non-limiting example. Graphite so treated is commonly referred to as expanded graphite.

[0164] The graphene platelet dispersion produced can be used to produce conductive materials. For example, it may be desirable to use these platelets to produce electrodes for electrochemical processes using a mixture of the platelet dispersion and a binder such as Nafion or PVDF, and coating the resulting mixture on the electrode surface. Electrodes produced in this manner can be used in batteries or electrochemical processes such as CO2 reduction.

[0165] In some embodiments, the produced graphene platelets can be further functionalized by attaching metal ions to either the functionalized edges or surfaces of the platelets. In some preferred embodiments, the metal ions are selected from iron, copper, cobalt, and tin.

[0166] The present disclosure will be better understood from the following examples of non-limiting embodiments of methods for producing the aforementioned graphene platelets.

[0167] In the first experiment, 100 mg of graphene with a purity of 99.9999% was suspended in a solution containing 2 mL of MeCN, 2 mL of EtOAc, and 2 mL of water; 222 mg (0.125 eq.) of NaIO4, and 4 mg (0.002 eq.) of RuCl3·xH2O. The resulting mixture was cooled using an ice bath and homogenized at 20000 rpm for 1 h. After this, the mixture was sonicated for 2 h, filtered, and washed with water and 1 M HCl until the filtrate was colorless. The filtrate was then washed with water until the filtrate was neutral. The filtrate was then freeze-dried to produce a black powder containing edge-functionalized graphene platelets.

[0168] In the second experiment, graphite (20 g, 1.67 mol) was suspended in MeCN (400 mL), EtOAc (400 mL) and water (600 mL). NaIO4 (71.2 g, 333 mmol) and RuCl3·xH2O (820 mg, 3.4 mmol, ca. 0.2 mol%) were added and the resulting mixture was cooled in an ice bath and homogenized (ca. 20000 rpm) for 1 h. The homogenizer was then removed and the mixture was sonicated for 2 h. The suspension was filtered and then the filtered solid was washed with water (100 mL) to remove excess 1 M HCl until the filtrate was colorless, then washed with water again until the filtrate was neutral. The resulting solid can be suspended in water and lyophilized or washed with ethanol and dried under vacuum to obtain the product as a black powder.

[0169] In these experiments, ruthenium tetroxide was formed with sodium periodate and ruthenium chloride, although it will be appreciated that other oxidizing agents, such as sodium hypochlorite, could be used instead.

[0170] It has also been found that longer lasting dispersions can be achieved by removing non-dispersible particles. This can be done by additional processing on the dried powder, including sonicating a dispersion of the dried powder in water for up to 30 minutes and allowing the resulting dispersion to stand for up to 48 hours or centrifuging the dispersion. The supernatant of the dispersion can then be decanted to remove the settled particles, and the supernatant can then be filtered to obtain the graphene powder. The powder can then be washed with an organic solvent, such as ethanol or acetone, and vacuum dried or freeze dried.

[0171] To characterize the platelets and confirm the presence of functional groups at the edges of each layer, several experiments were performed, which are described below.

[0172] The chemical structure of the produced graphene platelets was compared to that of bulk graphite using Raman spectroscopy. As shown in Figures 5A and 5B, the Raman spectra of the produced graphene platelets and 99.9999% pure graphite are shown, respectively. Both spectra show D bands 6, 6', G bands 7, 7' and 2D bands 8, 8'. Graphene structures produced by reduced graphene oxide typically show a D band larger than the G band, but this is not the case for the produced platelets. This suggests that the platelets are graphene in nature. Analysis of the 2D Raman bands of the edge and basal planes of the graphene plate, as shown in Figures 6A and 6B, respectively, allows the determination of the thickness metric M, which can be used to calculate the thickness metric M using the formula

number

[0173] This is further supported by the X-ray diffraction results, where the graphene platelet spectrum 9 substantially matches that of graphite 11, as shown in Figures 7A and 7B. XRD provides a measure of crystallinity, and graphite, which consists of many graphene layers, necessarily has a much higher degree of crystallinity than graphene platelets, which only have a few layers, so the reduced intensity is expected. The slight shift in the platelet spectrum 9 compared to graphite 11 is due to edge functional groups that increase the interlayer distance.

[0174] The presence of functional groups was investigated using X-ray photoelectron spectroscopy. This showed a composition of 94% C and about 6% O, again similar to graphite. The XPS spectrum shown in Figure 8 indicates the presence of three different types of C atoms, namely aromatic C at 284.5 eV (14 in Figure 8), phenolic C at 286.3 eV (13 in Figure 8), and carboxyl C at 289.8 eV (12 in Figure 8), suggesting the presence of carboxylic acid and phenolic groups. Thermogravimetric analysis was performed and the carboxylic acid content was calculated to be 0.15 milligram equivalents / g. High angle annular dark field (HAADF) scanning transmission electron microscopy showed bright edges that could be attributed to the presence of oxygen atoms at these positions, suggesting successful edge functionalization of the graphene platelets. The presence of both carboxyl and phenolic groups was further confirmed by titrating a dispersion of edge-functionalized graphene platelets in 0.1 M NaOH with 0.1 M HCl, as shown in FIG. 9, which shows two pKa values ​​at pH=4.2 and 8.0, which are attributed to the carboxyl and phenolic groups, respectively.

[0175] With the platelet structure established, experiments were carried out to measure the platelet's dispersibility and electrical conductivity, as well as their ability to be processed into polymer composites.

[0176] Edge-functionalized graphene platelets were found to be capable of being suspended in water at concentrations up to 700 mg / mL, as opposed to 0.55 mg / mL achieved by previous methods. Water suspensions of edge-functionalized graphene up to 10 mg / mL were found to be stable for at least 3 months. For suspensions above 10 mg / mL, settling of the platelets was observed in solution, but redispersion could be achieved by briefly shaking the solution. Suspensions of 100 mg / mL were found to be stable for at least 6 hours in water. Suspensions of 50 mg / mL were found to be stable for at least 6 hours in organic solvents such as toluene, ethanol, NMP, and DMF. Improved dispersibility was also observed in other solvents such as IPA, MeOH, CH2Cl2, DMF, and THF, suggesting that platelets may be highly dispersible in other solvents not explicitly mentioned.

[0177] For suspensions with a relatively high ratio of graphene platelets to solvent, the properties of the resulting solution may change. Suspensions of edge-functionalized graphene platelets with more than 25 wt% edge-functionalized graphene in water have been found to form pastes, while suspensions with more than 35 wt% edge-functionalized graphene in water have been found to form moldable doughs. The moldability of the resulting dough allows almost any shape to be molded from the material. Pastes are observed at 250 mg / mL in water, organic solvents, and ionic liquids. Doughs are observed at 350-700 mg / mL in water, organic solvents, and ionic liquids.

[0178] The edge-functionalized graphene platelets were formed into free-standing paper using vacuum filtration and the conductivity was measured by four-point probe conductivity measurement. The free-standing paper was found to have a highly desirable conductivity of 900 S / cm.

[0179] Alternatively, the generated platelet dispersion can be used to fabricate composites using polymers such as alginate, chitosan, PVA, PEG, PU, ​​PEI, PVDF or PEDOT PSS. In the first test experiment, 50 mg of platelets and 100 mg of polyvinyl alcohol (PVA) were stirred in 150 mL of water at 60 °C for 6–8 h until concentrated to 10–15 mL. Drop casting was then used to generate free-standing films of PVA-graphene platelet composites. In another proof-of-concept test for composite fabrication, a dispersion of 70% graphene platelets and 30% chitosan in water was 3D extrusion printed to form scaffolds.

[0180] The resulting platelet dispersion was also used to fabricate metal-functionalized graphene platelets. A proof-of-concept study was performed that consisted of mixing 0.1 mg / mL of iron chloride (FeCl3) solution with 1 mg / mL of the graphene platelet dispersion. The mixture was then stirred at room temperature for 30 min, before being centrifuged and washed with water to remove excess iron chloride, and then freeze-dried. This resulted in Fe-functionalized graphene platelets as measured by XPS and SEM images, with XPS showing 0.4 atomic % substitutional iron doping on the surface. The Fe-functionalized graphene platelets exhibited magnetic behavior.

[0181] Further functionalization was achieved by annealing the Fe-functionalized platelets at 750 °C for 1 h under N gas, resulting in the dispersion of iron / iron oxide nanoparticles across the platelet surface. Similar tests using copper chloride and tin chloride instead of iron chloride resulted in copper / copper oxide and tin / tin oxide nanoparticles binding to the platelets, respectively.

[0182] In the foregoing description of certain embodiments, specific terminology has been used for the sake of clarity, however, the present disclosure is not intended to be limited to the specific terminology so selected, and it is to be understood that each specific term includes other technical equivalents that similarly function to accomplish a similar technical purpose.

[0183] Additionally, the above describes only some embodiments of the invention(s), and alterations, modifications, additions and / or variations may be made without departing from the scope and spirit of the disclosed embodiments, which are illustrative and not limiting.

[0184] Moreover, while the invention(s) have been described in connection with what are presently considered to be the most practical and preferred embodiments, it should be understood that the invention is not limited to the disclosed embodiments, but on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the invention(s). Also, the various embodiments described above can be implemented in conjunction with other embodiments, for example, aspects of one embodiment can be combined with aspects of another embodiment to achieve yet further embodiments. Moreover, each independent feature or component of any assembly can constitute an additional embodiment.

[0185] Industrial Applicability As demonstrated herein, the edge-functionalized graphene thermal fluids of the present invention may enable conventional and future data center cooling systems to achieve significant improvements in heat rejection performance, energy savings and cost reductions.

Claims

1. 1. A composition for use as a thermal fluid, the composition comprising: a) a quantity of dispersed graphene platelets comprising a base layer of graphene, at least one discontinuous graphene layer being deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer being at least partially functionalized; b) containing a dispersion medium containing a certain amount of water; composition.

2. 2. The composition of claim 1, wherein the amount of the dispersed graphene platelets is from about 0.1 to about 6% by weight of the composition.

3. 10. The composition of claim 1, wherein the carrier fluid further comprises one or more co-solvents selected from glycols, alcohols, surfactants, dyes, defoamers, acids, bases, and the like.

4. The composition of claim 3, wherein the dispersion medium comprises water and the one or more co-solvents in a weight ratio of about 50:50 to 80:

20.

5. 10. The composition of claim 1, wherein the platelets are capable of forming a stable dispersion in water at a concentration of up to 700 mg / mL.

6. 10. The composition of claim 1, wherein the platelet has a conductivity of about 900 S / cm.

7. 10. The composition of claim 1, wherein the platelets are further functionalized by adding metal ions selected from Fe, Cu, Co, and Sn to at least one of the functionalized edges or surfaces.

8. 1. A composition for use as a thermal fluid, said composition comprising: a) a quantity of a polymer matrix composite comprising a polymer and dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) containing a dispersion medium containing a certain amount of water; composition.

9. 9. The composition of claim 8, wherein the amount of the dispersed graphene platelets is from about 0.1 to about 6% by weight of the composition.

10. 9. The composition of claim 8, wherein the carrier fluid further comprises one or more co-solvents selected from glycols, alcohols, surfactants, dyes, defoamers, acids, bases, and the like.

11. The composition of claim 10, wherein the dispersion medium comprises water and the one or more co-solvents in a weight ratio of about 50:50 to 80:

20.

12. 9. The composition of claim 8, wherein the platelets are capable of forming a stable dispersion in water at a concentration of up to 700 mg / mL.

13. 9. The composition of claim 8, wherein the platelet has an electrical conductivity of about 900 S / cm.

14. 9. The composition of claim 8, wherein the platelets are further functionalized by the addition of metal ions to at least one of the functionalized edges or surfaces.

15. 15. The composition of claim 14, wherein the metal ions are selected from Fe, Cu, Co and Sn.

16. The composition of claim 8, wherein the polymer is selected from alginate, chitosan, PVA, PEG, PU, ​​PEI, PVDF, PDMS or PEDOT PSS.

17. 1. A method of producing a composition for use as a thermal fluid, the method comprising: a) forming a quantity of dispersed graphene platelets comprising a base layer of graphene, at least one discontinuous graphene layer deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer being at least partially functionalized by suspending graphite or graphene in a solution comprising an organic nitrile (such as acetonitrile), an ester (such as ethyl acetate) and water, and reacting the solution containing the suspended graphite or graphene with an oxidizing agent (such as ruthenium tetroxide) to at least partially functionalize the edge regions of the graphite or graphene; b) forming a dispersion medium comprising a quantity of water; c) mixing said quantity of dispersed graphene platelets with said quantity of water, thereby producing a substantially homogenous composition.

18. 18. The method of claim 17, further comprising homogenizing the solution obtained in step b at 20,000 rpm for up to 2 hours.

19. 18. The method of claim 17, further comprising the step of sonicating the solution obtained in step b.

20. 18. The method of claim 17, further comprising the steps of filtering the solution obtained in step b to produce a filtered solid, washing the filtered solid, drying the filtered solid in vacuum to produce a dry powder, and freeze-drying the dry powder.

21. 21. The method of claim 20, wherein the dry powder is dispersed in water and sonicated for up to 30 minutes, the resulting mixture is allowed to stand for up to 48 hours to produce a solid and a supernatant, and the supernatant is decanted and filtered to produce the graphene powder.

22. 22. The method of claim 21, wherein the dry powder is dispersed in water, sonicated for up to 30 minutes, and the resulting mixture is centrifuged to produce a solid and a supernatant.

23. 18. The method of claim 17, wherein the oxidizing agent is ruthenium tetroxide obtained by reaction of sodium periodate with ruthenium chloride added to the solution containing suspended graphene or graphite.

24. 20. The method of claim 17, wherein the graphene or graphite is provided in the form of expanded graphite having increased interlayer spacing.

25. 22. The method of claim 21, wherein the graphene powder is then dispersed in a solution containing metal ions selected from Fe, Cu, Co and Sn to bond the metal ions to at least one of the surface or functionalized edges of the platelets.

26. 1. A method of producing a composition for use as a thermal fluid, the method comprising: a) forming a quantity of a polymer matrix composite comprising a polymer and dispersed graphene platelets comprising a base layer of graphene, wherein at least one discontinuous graphene layer is deposited on the base layer, the at least one discontinuous layer having a smaller surface area than the base layer, and edge regions of the base layer and the at least one discontinuous layer are at least partially functionalized; b) forming a dispersion medium comprising a quantity of water; c) mixing said quantity of dispersed graphene platelets with said quantity of water, thereby producing a substantially homogenous composition.

27. 27. The method of claim 26, further comprising homogenizing the solution obtained in step b at 20,000 rpm for up to 2 hours.

28. 27. The method of claim 26, further comprising the steps of sonicating the solution obtained in step b; washing the filtered solid; drying the filtered solid in vacuum to produce a dry powder; and freeze-drying the dry powder.

29. 27. The method of claim 26, wherein the dry powder is dispersed in water and sonicated for up to 30 minutes, the resulting mixture is allowed to stand for up to 48 hours to produce a solid and a supernatant, and the supernatant is decanted and filtered to produce the graphene powder.

30. 30. The method of claim 29, wherein the graphene powder is dispersed in water, sonicated for up to 30 minutes, and the resulting mixture is centrifuged to produce a solid and a supernatant.

31. 27. The method of claim 26, wherein the oxidizing agent is ruthenium tetroxide obtained by reaction of sodium periodate with ruthenium chloride added to the solution containing suspended graphene or graphite.

32. 27. The method of claim 26, wherein the graphene or graphite is provided in the form of expanded graphite having increased interlayer spacing.

33. 30. The method of claim 29, wherein the graphene powder is then dispersed in a solution containing metal ions selected from Fe, Cu, Co and Sn to bond the metal ions to at least one of the surface or functionalized edges of the platelets.

34. 18. The composition of claim 1 produced by the method of claim 17.

35. 27. The composition of claim 8 produced by the method of claim 26.

Citation Information

Patent Citations

  • Advanced thermal properties of a suspension with graphene nano-platelets (GNPS) and custom functionalized f-gnps

    US20140312263A1

  • Dispersible edge functionalised graphene platelets

    WO2020073081A1

  • Reinforced biodegradable polymer nanocomposite and method of manufacture thereof

    WO2021095023A1